Kajian teorI keterkaitan setting fisik dan identitas Kota dalam konteks City Branding - Putri, Marinda Noor Fajrina Noviana (Publica Scientific Solution, 2024)
City branding is very important for the growth and marketing of cities. Urban planning, visual communication, and graphic design are used to build a distinctive city identity that represents its values ??and goals. This research examines how city branding improves local economies and competitiveness around the world and how physical and non-physical variables shape city identity over time. This research examines city branding, city identity, and 'place fuzziness' using a comprehensive literature review. The aim of this research is to find out how the form of city identity, especially in tangible terms, supports city identity so that branding of a city can be achieved from an architectural and urban design perspective. The research results show that city branding can attract investment and tourists and strengthen the character and attractiveness of the city. A complex combination of physical and non-physical components forms a city's identity, which underlies city branding. This research also emphasizes the need to resolve 'place fuzziness'—unclearness of a place's identity or function—to improve city branding. This research suggests that city planners and marketers must work together to ensure that physical development and social activities promote a city's identity, eliminate ambiguity, and improve its image. Creating a vibrant and sustainable city image requires integration and strategic planning in city branding and identity management.